"A jungle that is continually encroaching": The time of disaster management. (February 2018) - Hu, Cameron
This essay examines the temporal logics of contemporary disaster management. I discuss episodes from the expansion of the global disaster management complex—in the United States after WWII, and in Indonesia after the New Order—to characterize the form of futurity established through the technocratic administration of systematically-envisioned catastrophe. Disaster management projects a shallow future whose indeterminacy does not stimulate aspiration toward transcendence of the given, but rather motivates an endless procedural loop of anticipation and pre-emption in order to delay the destruction of the present order. Disaster management thus refashions "action" as the postponement of the future, and in doing so explicates a basic but neglected temporality of liberalism—that of vigilance toward continually-renewed danger.